Analisis Daya Dukung Wisata Pantai Libuo Kecamatan Paguat Kabupaten Pohuwato - Kazmir Bawu; Sunarty Suly Eraku; Nurdin Mohamad (-, 2026)
Libuo Beach is a coastal tourism destination in Paguat Subdistrict, Pohuwato Regency, used for camping, beach recreation, and relaxation. Increasing use of tourism space requires information on area capacity to prevent visitor activities from reducing environmental quality and visitor comfort. This study aims to describe existing conditions, identify visitor space and time requirements, estimate the physical carrying capacity of each activity, and formulate management directions. A descriptive quantitative approach was employed. Primary data were obtained through observation, effective-area measurement, facility inventory, documentation, and questionnaires administered to 58 visitors, consisting of 18 camping respondents, 20 beach-recreation respondents, and 20 relaxation respondents. Carrying capacity was calculated using DDK = K × (Lp/Lt) × (Wt/Wp). Based on the parameters applied, the estimated capacity was 75 persons per day for camping, 8 persons per day for beach recreation, and 177 persons per day for relaxation. The relatively low capacity for beach recreation was influenced by the recorded effective area and its larger spatial requirement. These results demonstrate that capacity varies according to spatial use and activity duration. Management should prioritize activity zoning, actual visitor recording, camping control, cleanliness, swimming safety, and environmental monitoring. The results represent estimates of physical carrying capacity and should be compared with actual visitation and ecological and social indicators before being adopted as operational quotas.